Isatin 3-benzoylhydrazone: an orthorhombic form - Ali, Hapipah Mohd; Ng, S.W.; Halim, S.N.A. (International Union of Crystallography, 2005)
The amine N atom of the isatin portion of the title compound (systematic name: 2-oxo-2,3-dihydro-1H-indole-3-carbaldehyde benzoylhydrazone), C15H11N3O2, forms a hydrogen bond with the amide O atom of the benzoylhydrazone portion of a symmetry-related molecule to give rise to a hydrogen-bonded chain structure that propagates by a twofold screw axis along the a axis of the orthorhombic unit cell.